2019
DOI: 10.20937/atm.2019.32.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dust deposition rate and soil characteristics in an arid region of Iran

Abstract: La formación de polvo es uno de los procesos que causan mayor impacto ambiental en zonas áridas y semiáridas. En este estudio se utilizó el algoritmo para la detección automática de interacción de chi-cuadrado (CHAID, por sus siglas en inglés) para determinar las relaciones no lineales entre las propiedades físicas y químicas del suelo y la tasa de sedimentación de polvo (TSP) tanto estacional como anual en la subcuenca del pantano de Gavkhouni, Irán central. Los resultados se compararon con los obtenidos por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Results showed that street dust in Lublin did not show contamination with Cr, Ni and Pb (Zgłobicki et al, 2019). Aghasi et al (2019) studied the relationship between soil characteristics and dust deposition rate in Gavkhouni swamp sub-basin located in Central Iran. Results showed that particle size distribution of surface soil, especially sand content is an important factor which affects seasonal and annual DDR (Aghasi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that street dust in Lublin did not show contamination with Cr, Ni and Pb (Zgłobicki et al, 2019). Aghasi et al (2019) studied the relationship between soil characteristics and dust deposition rate in Gavkhouni swamp sub-basin located in Central Iran. Results showed that particle size distribution of surface soil, especially sand content is an important factor which affects seasonal and annual DDR (Aghasi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aghasi et al (2019) studied the relationship between soil characteristics and dust deposition rate in Gavkhouni swamp sub-basin located in Central Iran. Results showed that particle size distribution of surface soil, especially sand content is an important factor which affects seasonal and annual DDR (Aghasi et al, 2019). Ahmadi Doabi et al 2017 No significant association was observed between variables such as temperature, humidity, wind speed and dust concentration, whereas a significant association was found between precipitation variable and dust concentration.…”
Section: Introductionmentioning
confidence: 99%